Dėl lie. ãmas - Kregždys, Rolandas (Baltistica, 2002)
Concerning Lith. ãmas On the basis of the data collected from LKŽ (Dictionary of the Lithuanian Language including card index) and from the Corpus of present day Lithuanian compiled at VytautasMagnusUniversity(http:// donelaitis.vdu.lt) the following conclusions can be drawn: 1. Lith. ãmas is characterized not only by the meanings ‘voice, speech and dog’ (cf. LKŽ), but by the meanings ‘strength’, ‘consciousness etc.’, as well. 2. There seem to be two homonymous nouns: 1. ãmas ‘dog’, which is to be regarded as an onomatopoeic noun, and 2. ãmas ‘voice, speech; strength; consciousness, etc’ which is to be treated as a polysemous noun. 3. Lith. 2. ãmas ‘voice, speech; strength; consciousness, etc’ is to be analysed proceeding from possible parallels in Indo-Iranian and probably other I.-E. languages.